Psychological Component in the Context of Endometriosis with Involvement of the Gastrointestinal Tract: A Case Study - K. S. A. Azevedo, Larissa; B. Domiciano, Carolina; C. Filho, Aníbal; Cecília Maia, Ana; C. Neto, Geraldo; H. C. N. Felipe, Daniel; F. C. Cavalcanti, Amanda; C. M. Lima, Camila; C. N. Oliveira, Deborah (Clinical Medicine And Health Research Journal, 2023)
Endometriosis is one of the most prevalent gynecological comorbidities in women of reproductive age and has a significant impact on mental health. The aim of this study is to report a case of a patient with endometriosis with ovarian and intestinal involvement who had a signiﬁcant psychological component, presenting depressive symptoms and anxiety crises. The patient presented atypical symptoms, characterized by frequent nausea, recurrent vomiting, and sialorrhea, which required a sensitive and more critical look from the professionals who followed her, so that the treatment could be individualized and effective. She referred to dysuria, dyschezia, bloating, deep dyspareunia, and associated with these symptoms, the patient also reported pelvic pain, asthenia, and loss of about 10 kilos during this period. Imaging exams were performed, which showed endometriosis with ovarian and intestinal involvement, and from this she underwent surgical procedure for resection of the endometriosis foci and subsequent and anatomopathological study of the specimens, confirming the diagnosis. After the surgical management, the patient reported a decrease in symptoms, but still had signs that did not allow a complete improvement, leading her to add a psychological and psychiatric treatment, which made all the remaining symptoms and atypical for endometriosis disappear. This demonstrates the importance of the intervention in the treatment for endometriosis being done in a complete and multiprofessional manner.